Pengembangan Media Pembelajaran Interaktif Berbasis Etnosains dan Nilai Spiritual untuk Meningkatkan Pembelajaran IPAS di Sekolah Dasar - Ummu Kholifatul Khasanah; Muhammad Iqbal; Zahraini Zahraini (Lembaga Teewan Journal Solutions, 2026)
This study aims to develop an interactive learning media based on ethnoscience integrated with spiritual values for elementary school IPAS learning, as well as to examine its feasibility and effectiveness in improving students’ learning outcomes. However, previous studies on interactive learning media in elementary IPAS tend to focus primarily on technical features without integrating local cultural contexts and spiritual values, resulting in less meaningful learning experiences. Therefore, this study offers a novel approach by integrating ethnoscience and spiritual values into gamified interactive media. The research employed a Research and Development (R&D) approach using the 4D model, which includes the stages of define, design, develop, and disseminate. The participants consisted of 28 fifth-grade students at SD Negeri 27 Banda Aceh. Data were collected through observation, questionnaires, interviews, and learning achievement tests. The findings revealed that the developed media achieved a validity level of 90%, categorized as highly valid. In terms of effectiveness, students’ learning outcomes improved significantly, as indicated by the increase in the average pretest score from 65.00 to 90.18 in the posttest, with an N-Gain score of 0.72 (high category). Furthermore, students’ responses toward the media reached 91.9%, indicating a very positive perception. Therefore, the interactive learning media based on ethnoscience and spiritual values is considered both feasible and effective for use in elementary school IPAS learning.